The State Correction Officer as Keeper and Counselor: An Empirical Investigation of the Role - Black, Clifford M. (1981)
This paper addresses two essential research needs in criminal justice literature: (1) the need for an assessment of the content of the role of block officer; and (2) the need for an empirical test of the presumed irreconcilable goals of custody and treatment as these are embedded in the role of state correction officer. A Task Inventory approach was adapted and a random sample of 100 correction officers in four heterogeneous state institutions were interviewed. Results of the study reveal that custodial staff spend at least sixty-percent of their on-job time performing duties not classified as security in nature. Results of the study challenge many of the existing stereotypes of correction officers in the literature. *Th